Third millennium ergonomics: human factors in objects, built environments and city design (2011)
The article presents a meditation on the importance and the role played by physical and non-physical ergonomics in third millennium cities and architecture, the knowledge societies providing the scenario for all human groups, including infants, the elderly and the disabled. The author emphasizes on three human factors to be met when designing i) objects: simplicity, user logic; ii) built environments: barriers, function distribution; and iii) cities: accessibility and urban ergonomics.